Quantifying aperture, spacing and fracture intensity in a carbonate reservoir analogue: Crato Formation, NE Brazil. (November 2018) - Miranda, T.S.; Santos, R.F.; Barbosa, J.A.; Gomes, I.F.; Alencar, M.L.; Correia, O.J.; Falcão, T.C.; Gale, J.F.W.; Neumann, V.H.
Abstract: The characterization of fracture networks in carbonate reservoirs represents a primary approach to understand the processes of fluid flow. The study of outcrop analogues has been used to enhance the understanding of the relative contribution of fracture networks to reservoir permeability. The outcrop data can overcome scale limitations and/or lack of consistency of subsurface datasets (e.g. seismic, well logs, and cores). This paper presents the fracture characterization of the Aptian-Albian lacustrine laminites of Crato Formation (Araripe Basin, NE Brazil), which have been investigated as an analogue to some of the observed carbonate facies present in the pre-salt reservoir sequence of the Brazilian marginal basins. In order to provide fracture attributes for Discrete Fracture Network (DFN) modelling we investigate spacing and aperture distribution, length and intensity of fractures based on the use of traditional scanline (macro and microscale) method. The main fractures identified in the Crato Formation are shear and extensional fractures and with stylolites also present. In this study, we focused on vertical veins, which strike in two principal directions, NNW-SSE (Set 1), NE-SW (Set 2), and are filled or partially filled by calcite or gypsum. The relationship between length and aperture of vertical veins is linear. Apertures and spacings of fractures in both sets 1 and 2 follow power law and lognormal cumulative frequency distribution functions, respectively. Fractures of Set 2 are more likely to be clustered than are fractures of Set 1, which have a wider kinematic aperture. This structural database can be used to populate computational models that consider the widespread fracture system in the fluid flow simulation of carbonate reservoirs. Highlights: Powerful Pre-Salt reservoir analogue located in NE Brazil. Detailed deformation history derived from the characterization of extensional fracture attributes. Upscalable importance and relevance to driving future research on major Brazilian carbonate reservoirs. Detailed description of the statistical estimation on the distribution of fracture attributes.